An Experimental and Theoretical Study of the Impact of the Precursor Pulse Time on the Growth Per Cycle and Crystallinity Quality of TiO2 Thin Films Grown by ALD and PEALD Technique - Chiappim, William; Fraga, Mariana Amorim; Maciel, Homero Santiago; Pessoa, Rodrigo Sávio (Frontiers in Mechanical Engineering, 2020)
In this paper, theoretical and experimental approaches were used to evaluate the impact of the precursor’s pulse time on the growth per cycle (GPC) and on the crystallinity quality of atomic layer deposited TiO2 thin films on Si(100) and FTO substrates. In theoretical investigation, we employ a general model that can be applied to both metal and oxidant precursors, and it is based on the Maxwell-Boltzmann velocity distribution from which the molecular flux of gases that collide with the substrate is deduced to adjust the experimental characteristics of GPC versus pulse time. This model allowed us to adjust the GPC of TiO2 films produced by thermal atomic layer deposition and by plasma-enhanced atomic layer deposition under different deposition parameters and substrates. In experimental investigation, the influence of GPC on the chemical and structural properties of TiO2 thin films was evaluated by Rutherford backscattering spectroscopy, grazing incidence x-ray diffraction and ellipsometry techniques. In thermal mode, using H2O as an oxidant precursor, the stoichiometry of TiOx films has an x value of 1.98 from the GPC saturated regardless of the metal precursor or substrate used. In addition, using O2 plasma, a super-stoichiometric film with x values from 2.02 to 2.30 is obtained. In thermal mode, the GPC saturated and film thickness are, on average, 40% higher for TiCl4 compared to TTIP precursor. Using O2 plasma, the growth per cycle saturated is approximately twice as high the thermal mode using TTIP precursor. For both atomic layer deposition modes, the crystallinity degree showed values of 50% to 80% for TiCl4 in the temperature range of 250 to 350 ºC. On the other hand, for TTIP, it was below 40% in thermal mode and between 80 and 95% in plasma mode (250 ºC). It was observed that the reaction rate, the diffusion coefficient and the molecular flux are inversely proportional to the temperature. These results evidenced that the crystallinity and epitaxial quality of the TiO2 film are higher for TTIP using O2 plasma. However, a better stability of the parameters analyzed for TiCl4 in the two atomic layer deposition modes was verified.